CFD modelling of diffusive-reactive transport of ozone gas in rice grains - Silva, Marcus Vinicius de Assis; Martins, Márcio Aredes; Faroni, Leda Rita D'Antonino; Vanegas, Jaime Daniel Bustos; Sousa, Adalberto Hipólito de (Biosystems Engineering, 2019)
The search for alternatives to the use of chemical products to control insect pests in stored grains has stimulated the development of new techniques that allow the maintenance and preservation of grain quality without posing risks to people and the environment. One of these alternatives is the use of ozone gas (O3) as a fumigant, mainly due to its oxidising and biocidal characteristics. To investigate the transport mechanisms involved in the flow of the O3 gas through rice grains, the CFD (Computational Fluid Dynamics) analysis was used, and from this evaluation, it was possible to predict the decomposition reaction constant and the O3 effective diffusion coefficient. In the experiment, grains were submitted to fumigation process in a prototype adapted from a diaphragm cell. Data on the ozone gas concentration were collected from a monitoring point immediately above the grain layer every 10 min. Parallel to the experimental procedure, the modelling of the O3 gas flow using the CFD technique was performed. The adjustment parameters input to the CFD model were the effective diffusion and the decomposition reaction constant of the O3 gas in the rice grains. The estimated diffusivity value (1.0 × 10−6 m2 s−1), and decomposition reaction constant (0.00167 s−1) are of the same order of magnitude of several other gases for agricultural grains.
Keywords: Computational fluid dynamics; Diaphragm cell; Oryza sativa; Ozonisation; Storage of grains